THE ESSENCE OF GEOGRAPHIC IN SHAPING STUDENT'S THINKING PARADIGMS - Fahyumi Rahman (JURNAL GEOGRAFI, 2021)
The paradigm of thinking about geography has an essential shift that categorizes the supporting sciences of geography in a separately. These problems have to resulted in the existence of geography not being discussed in a full, which includes physical and humans aspects. On the other hand, the formation of a geographical thinking paradigm in the learning only focuses on knowledge of what and where a phenomenon occurs. Whereas the design of geography learning must be constructive and in line with the capabilities of geography (geocapabilites) in reconstructing the essence of geography in the comprehensive manner. This article tries to revitalize the essence of geography and the formation of student high school paradigms in learning into restore the integrity of geography as a science. In essence, geography puts more emphasis on a unique way of studying the earth with a variety of assistive sciences in the perspective of geography eyes (a geographical point of view includes: spatial, environmental, and complex areas). The geography learning design that is designed must be focus on the ability of students to construct (constructively) and correlate each relationship with the meaning of the nature of geography.